A COMPARATIVE STUDY OF SALICYLALDOXIME, CYSTEINE AND BENZOTRIAZOLE AS INHIBITORS FOR THE ACTIVE CHLORIDE-BASED CORROSION OF COPPER AND BRONZE ARTIFACTS - Abu-Baker, Ahmad N.; MacLeod, Ian D.; Sloggett, Robyn; Taylor, Russell (European Scientific Journal, ESJ, 2013)
This study aimed to investigate the effectiveness of salicylaldoxime and cysteine as potential replacements to benzotriazole, the widely used but environmentally unfriendly and not always effective copper corrosion inhibitor. Coupons of modern copper, 5% tin bronze, and 12% tin bronze samples were corroded using an accelerated electrochemical procedure, which involved anodically polarizing the coupons in a solution of 0.5M NaCl + 0.1M CuCl2.2H2O. X-ray diffraction analysis of the corrosion products showed the presence of copper (I) chloride (CuCl) on the surfaces of the three reference materials. Tin (IV) oxide (SnO2) was also detected on the surface of the 12% tin bronze. The interaction of the corrosion inhibitors with the corrosion products was investigated by visual examination and scanning electron microscopy. Benzotriazole and salicylaldoxime formed a surface adherent and aesthetically acceptable green complexes for the corroded copper and bronze, while cysteine formed grey patches that cover the green corrosion on copper and bronze. Accelerated corrosion in an environmental chamber of high relative humidity and temperature (84% RH and 38oC) showed that salicylaldoxime was the most effective inhibitor for the three reference materials against corrosion in these severe environmental conditions. However, electrochemical impedance spectroscopy's results showed that the benzotriazole was the most effective inhibitor in chloride solutions, and that the effective of cysteine increases with the increase of tin content in the alloy. It was concluded that salicylaldoxime presented a relevant and effective corrosion inhibitor for most conservation applications on corroded copper and bronze, while cysteine presented an environmentally friendly replacement for benzotriazole to protect uncorroded or previously treated by reduction back to metal artifacts.